Clinicopathological characteristics with EGFR, ALK, ROS1 genetic alternation and prognostic analysis of primary lymphoepithelioma-like carcinoma - Shen, Yinchen; Hu, Fang; Zhang, Bo; Li, Changhui; Zhang, Xueyan; Han, Baohui (Translational Cancer Research, 2019)
Background: Primary lymphoepithelioma-like carcinoma (LELC) is a rare form of lung cancer, since genetic alternations participate in the carcinogenesis in lung cancer, whether critical driver genes such as ROS1 fusion, anaplastic lymphoma kinase (ALK) rearrangement and epidermal growth factor receptor (EGFR) mutation play roles in LELC remains unclear. Methods: We collected a total of 30 LELC samples for genetic and prognosis analysis retrospectively in Shanghai Chest Hospital, EGFR gene mutation, ALK rearrangement and ROS1 fusion status were extracted from digital database. Clinicopathological characteristics with genetic profiling and survival were analyzed. Results: All samples appeared negative for genes (EGFR, ALK and ROS1) alternations detection. Female gender acted as an independently prognostic factor in poorer disease-free survival (DFS) (P=0.034), and tumors locate in the left lobe associate with worse DFS in univariate analysis (significant trend, P=0.051), moreover, serum positive NSE level also indicate a shorter DFS after adjustment (significant trend, P=0.057). Most of LELC are diagnosed at early stage, with 90.0% (27/30) patients obtained the opportunities for surgery. Conclusions: Since no classical genetic alternations appeared in present study, more investigations of other genes distributions should be explored in the future for better understanding of this rare subtype of lung cancer. Serum positive neuron-specific enolase (NSE) level seemed to be a prognostic biomarker for DFS in LELC patients.